Gambogic Acid and Its Analogs Inhibit Gap Junctional Intercellular Communication - Choi, Eun J.; Yeo, Joo H.; Yoon, Sei M.; Lee, Jinu (Frontiers in Pharmacology, 2018)
Gap junctions are intercellular channels composed of connexins. Cellular molecules smaller than 1 kDa can diffuse through gap junctions by a process termed gap junctional intercellular communication (GJIC), which plays essential roles in various pathological and physiological conditions. Gambogic acid, a major component of a natural yellow dye, has been used as traditional medicine and has been reported to have various therapeutic effects, including an anti-cancer effect. In this study, two different gap junction assay methods showed that gambogic acid and its analogs inhibited GJIC. The inhibition was rapidly reversible and was not mediated by changes in surface expression or S368 phosphorylation of Cx43, cellular calcium concentration, or redox state. We also developed an assay system to measure the intercellular communication induced by Cx40, Cx30, and Cx43. Dihydrogambogic acid potently inhibited GJIC by Cx40 (IC50 = 5.1 μM), whereas the IC50 value of carbenoxolone, which is known as a broad spectrum GJIC inhibitor, was 105.2 μM. Thus, dihydrogambogic acid can act as a pharmacological tool for the inhibition of Cx40.